(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In the article it is said about the communicative function of folklore. The author thinks that the communicative function of folklore, in general, is settled with the conception of the social dynamics. In the article it is said about the communicative relations of folklore with the social dynamics indetails. As is well known, anonymity, orality, and collectivity, as well as the traditionality of folklore, as the main features that determine folklore, are in display status. The author dwells on such problems as the causes of these signs, why folklore is an anonymous, collective, oral and traditional culture, what factors determine these signs for a folk culture.The given thought sare looked through from the point of the functional structure aspect of folklore. The diachronic and synchronic functionality conception sare also explained in the article.